A külföldi egyetemisták szabadidő-eltöltési és térhasználati mintázatai Szegeden = Spatial patterns of leisure activities in Szeged - Bence, Miklós; Nagy, Gyula; Karl, Máté János (Közép-Európai Közlemények, 2018)
One of the cornerstones of the education policy of the European Union is the promotion of educational mobility among member countries, enabling students to study abroad. Students can gain valuable knowledge from which they can benefit on the labor market and the related higher education institutions can strengthen their international relations. The mass presence of foreign students has an impact on the local economy and the services of the reception area. In the life of Szeged foreign students have also special importance. A recent study in connection with student-mobility in three cities – Debrecen, Pécs and Szeged – found that foreign students have a positive impact on the economy of the cities, through their spending they improve the local employment and create jobs. However in the case of Szeged the limitation of recreational and leisure activities was identified as a problem. This offers many urban development potential and directions for decision-makers and local entrepreneurs. The exploitation of these potentials could enhance the positive effects of foreign students on the local economy, as well as help to improve the urban image, thus strengthening the tourist significance of Szeged. This paper shows the overall impact of foreign students on the life of the reception area. We outline this by presenting the results of a baseline survey research. The research attempts to explore the background of the problems that have already been formulated in order to provide a starting point for later research and, secondly, to offer development directions in itself through the suggestions of foreign students.